Sofrimento de indeterminação e reconhecimento perverso: um estudo da construção da personagem doente mental a partir do sintagma identidade-metamorfose-emancipação - Lima, Aluísio Ferreira de (2009)
This is a thesis of Critical Social Psychology which main focus was to unveil, based on the theory of identity proposed by Antonio da Costa Ciampa expressed in the identitymetamorphosis- emancipation sintagma, how the construction of the mentally ill character occurs considering the recognition of different social actors and the relation set with the mental health discourse proposed by the psychiatric reform. The research was divided into tree named routes: historical route, theoretical route, empirical route. In the first route we make a presentation of the historical development of the dual normal/pathological conception, which culminated in the construction of the assumed identity of the mentally ill, and analyze this development in light of the different institutional articulations and policies (especially the relationship between psychiatry and Social Psychology) legitimized from laws and decrees that allowed the Brazilian Psychiatric Reform. Then, we point out how the theory of identity proposed by Ciampa is inserted in the tradition of Critical Social Psychology and cross the contribution of critical theory, especially the habermasian theory. All this to think about the conditions for human emancipation to unveil the strong investment of technical and psychological discourses suffered by the identity and which produce fetishized characters sustained by perverse recognition. Then, we bring the life history narratives of Ana, Gabriel and Francisco, which offered evidence of how individuals have appropriated the discourse of mental illness to organize and represent their identities today. In this moment, which point out that we can not cynically sustain, by using the discourse of mental illness from an anti-asylum politics, that we are enabling the empowerment of individuals. We need to adopt a post-conventional recognition (parallax view) to not reproduce perverse recognition